EFEKTIFITAS METODE JARIMATIKA DALAM PEMBELAJARAN OPERASI HITUNG PERKALIAN BAGI ANAK SEKOLAH DASAR/ MADRASAH IBTIDAIYAH - Suparni Suparni (IAIN PADANGSIDIMPUAN, 2018)
Using the Jarimatika method to improve students' numeracy skills in counts ranging from 6 to 20. Jarimatika is very easy to accept students, learning does not burden computer memory and tools can be used easily in fronst of students. Students aged 6 years to 12 years are only able to think logically or be able to solve problems that characterize them concretely or by talking about and doing things. Therefore, students will more easily think of something visual from verbal. Thus students will be able to optimize the abilities of each student. With continuous training, it will activate brain cells. The application of the Jarimatika method is very helpful for students, because so far students only count the multiplication by memorizing or summarizing repeatedly, requiring considerable time, besides that most students are not careful in adding them up.